2018
DOI: 10.3390/molecules23102410
|View full text |Cite
|
Sign up to set email alerts
|

An Ab Initio QM/MM Study of the Electrostatic Contribution to Catalysis in the Active Site of Ketosteroid Isomerase

Abstract: The electric field in the hydrogen-bond network of the active site of ketosteroid isomerase (KSI) has been experimentally measured using vibrational Stark effect (VSE) spectroscopy, and utilized to study the electrostatic contribution to catalysis. A large gap was found in the electric field between the computational simulation based on the Amber force field and the experimental measurement. In this work, quantum mechanical (QM) calculations of the electric field were performed using an ab initio QM/MM molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…7 From these experiments, they established a linear correlation between the strength of the electric fields in the active site and the activation free energy of the reaction, and a direct connection between the strength of a hydrogen bond and the electric field it exerts. 7 Subsequent theoretical studies have found support for the idea that electric fields strongly correlate with the efficiency of the catalytic process for KSI 18 . Markland and co-workers used ab initio path integral molecular dynamics (MD) simulations to further characterize KSI's active site hydrogen bond network, 19 observing enhanced proton flexibility within the active site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 From these experiments, they established a linear correlation between the strength of the electric fields in the active site and the activation free energy of the reaction, and a direct connection between the strength of a hydrogen bond and the electric field it exerts. 7 Subsequent theoretical studies have found support for the idea that electric fields strongly correlate with the efficiency of the catalytic process for KSI 18 . Markland and co-workers used ab initio path integral molecular dynamics (MD) simulations to further characterize KSI's active site hydrogen bond network, 19 observing enhanced proton flexibility within the active site.…”
mentioning
confidence: 99%
“…The results presented thus far are based on average values of the field, similarly to what can be found in previous literature on KSI. 5,8,18,21 But because enzyme function is also governed by different time scales [22][23][24] , then it might be expected that electric field fluctuations both in the active site and from the surrounding protein environment will modulate the enzyme activity. 25 Even rigid proteins undergo small backbone displacements [26][27] that in turn promote concerted side chain rearrangements [28][29][30][31] that can be important for catalytic function [32][33] .…”
mentioning
confidence: 99%
“…Next, the theoretical fundamental of possessing two MbCO B states is explored. In previous works 22,74,78 , it was indicated that the two B states are stabilized by the electrostatic interactions between the CO and its surroundings and that the splitting of the infrared spectrum is derived from the Stark effect where the photodissociated CO in the same docking site experiences the electric field with antiparallel orientations. The conclusions suggest that there may be a specific relationship between the electrostatic interactions and the electric fields.…”
Section: Resultsmentioning
confidence: 99%
“…S1 †) reduce the DG ‡ of the reaction, and are extensively reported as supporting the electrostatic TS stabilization mechanism. 18,[20][21][22] By contrast, many studies propose that enzymes can catalyze reactions through destabilizing the GSs of reactions. [23][24][25] Ruben, et al reported that, in the KSI-catalyzed isomerization of 5-AND, desolvation of the COO À group of Asp40 partially catalyzes the reaction via GS destabilization (Fig.…”
Section: Introductionmentioning
confidence: 99%